Finance, taxes and provenance : a German museum acquisition of Chinese antiquities in 1935 - Zur Mühlen, Ilse von (Journal for art market studies, 2018)
Research for this article was initially prompted by a restitution claim for several early Chinese objects, which had been acquired by the Bavarian State Ethnological Museum, now Museum Fünf Kontinente in Munich, at two sales in the Berlin auction house of the Jewish art dealer Paul Graupe in 1935.The title of the auction catalogue explained the circumstances of the forthcoming sale. The stock of the firm Dr. Otto Burchard & Co, Berlin was to be liquidated, with Chinese art in catalogue volume I, offered on 22 and 23 March 1935 (catalogue no. 140) and a further section catalogued in volume II, offered on 29 April 1935 (catalogue no. 143). From the wording on the catalogue cover, it seemed clear that an art dealing firm was in liquidation and that its stock in trade was being auctioned at Paul Graupe's. At the sale, the museum bid successfully on thirty-eight artefacts. In addition, two sculptures were donated to the museum after the Second World War which had been bought at the same sale by third parties.The need for investigation raised questions about the reasons that had prompted the auctions and the liquidation of the firm Dr. Otto Burchard in the first place, and about the previous provenance of the Chinese objects.